2018
DOI: 10.1055/a-0655-1987
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening program using FIT: quality of colonoscopy varies according to hospital type

Abstract: Background and study aims  To compare the quality of colonoscopy in a population-based coordinated program of colorectal cancer screening according to type of hospital (academic or non-academic). Patients and methods  Consecutive patients undergoing colonoscopy after positive FIT (≥ 20 ug Hb/g feces) between January 2009 and September 2016 were prospectively included at five academic and seven non-academic public hospitals. Screening colonoscopy quality indicators considered were adenoma detection rate, cecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…The harm caused by colonoscopies in our FIT program is in line with that recently reported by two other programs (▶ Table 5) [7,8,[15][16][17][18]. Their rates of 7.0 ‰ and 10.0 ‰, along with our 11.9 ‰ rate of complications requiring hospitalization, are notably higher than the maximum standard of 5 ‰ for 7day hospital admission/readmission rate recommended by the ESGE [9].…”
Section: Discussionsupporting
confidence: 88%
“…The harm caused by colonoscopies in our FIT program is in line with that recently reported by two other programs (▶ Table 5) [7,8,[15][16][17][18]. Their rates of 7.0 ‰ and 10.0 ‰, along with our 11.9 ‰ rate of complications requiring hospitalization, are notably higher than the maximum standard of 5 ‰ for 7day hospital admission/readmission rate recommended by the ESGE [9].…”
Section: Discussionsupporting
confidence: 88%
“…Approximately one-third of colonoscopies were withdrawn within 6 minutes and had incomplete photo-documentation. Although the overall rate of cecal intubation exceeded 90%, the cecal intubation rate of non-board-certified According to previous studies conducted in Spain and the United States comparing the quality of colonoscopies between various practice settings, both academic and non-academic centers provided high-quality colonoscopies [14,15]. Our results, unlike previous studies, showed that the quality of colonoscopies in community hospitals and nonhospital facilities was suboptimal.…”
Section: Discussioncontrasting
confidence: 79%
“…In Spain, all screening colonoscopy data are coded by the coordinating staff in the Basque Country CRC Screening Program. In this way, data on colonoscopy quality indicators including ADR, cecal intubation rate, complications, and bowel preparation quality can be collected [14,29].…”
Section: Discussionmentioning
confidence: 99%
“…The BCSP is based on Primary Health Care (PHC), where most of the preventive and health promotion activities are carried out. A full description of this programme can be found as reported by Portillo et al (7).…”
Section: Introductionmentioning
confidence: 99%